PIROLISIS LIMBAH PANGKAL BAMBU MENJADI KARBON AKTIF DAN ASAP CAIR MENGGUNAKAN ZAT AKTIVATOR ASAM PHOSFAT - Ani Purwanti; Sumarni -; Ade Alvian A (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2017)
An inefficient utilization of bamboo resulted in bamboo base as waste without economical value. Converted this bamboo waste becomes active carbon through pyrolysis will add more value of the product. This study aims to determine the parameters which influence the pyrolysis of bamboo waste, to determine the activity of the obtained active carbon and liquid smoke yield. The preparation of raw material was conducted by cutting the bamboo into the size of an average length of 4.33 cm, 1.43 cm wide, and 0.48 cm high, also analyzed the water content. Pyrolisis was done for 60 minutes in the range of temperature between 250°C to 450°C. Activation methods varied by soaking in diluted phosphoric acid solution (6-14%) prior to pyrolysis with variations in dipping time and temperature pyrolysis. Yield and reactifity of obtained active carbon and also yield of liquid smoke were analyzed. With 100 gram of raw material, 60 minutes of reaction time, and activation for 24 hr resulted in an optimum yield of active carbon 27,43% with reactivity 433,99 mg/g under 12% of phosphoric acid solution at 450°C, and the yield of liquid smoke was 54 mL. GC-MS results showed that acetic acid (30.33%) as a major component, while 2-propanone (14,34%), methanol (10,37%), 2-butanone (3,75%) acetaldehyde (3,59%), furfural (2,95%), corylon (2,21%), cyclopropyl carbinol (2,11%), phenol (2,1%), glycol (1,85%), dan carbonic acid (1,28%) as a minor component.